2008
DOI: 10.1007/s11663-008-9142-x
|View full text |Cite
|
Sign up to set email alerts
|

A Semi-empirical Mathematical Model to Estimate the Duration of the Atmosphere within a Double Oxide Film Defect in Pure Aluminum Alloy

Abstract: It has been shown that the oxygen and nitrogen within the atmosphere of a double oxide film defect can be consumed by the surrounding Al melt. Experimentally determined reaction rates were used to construct a semi-empirical model to predict the change in volume with time of a bubble of air trapped in an Al melt, with the model including the diffusion of H from the metal into the bubble. Comparison with experimental results showed that the model predicted the change in volume well. The model was then used to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 5 publications
2
32
2
Order By: Relevance
“…However, the oxide film defects could also be expanded again because of a variety of effects, such as the precipitation of dissolved hydrogen from the surrounding melt into the internal atmosphere of the defect and strains in the liquid metal because of solidification shrinkage. [1][2][3][4] To understand the behavior of entrained double oxide film defects Raiszadeh and Griffiths [5] held a known volume of air in a melt of commercially pure liquid aluminum, and they recorded the change in its volume with time using real-time X-ray radiography. These results showed that, first, the oxygen of the trapped air bubble reacted to form Al 2 O 3 , and then, second, the nitrogen reacted to form AlN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the oxide film defects could also be expanded again because of a variety of effects, such as the precipitation of dissolved hydrogen from the surrounding melt into the internal atmosphere of the defect and strains in the liquid metal because of solidification shrinkage. [1][2][3][4] To understand the behavior of entrained double oxide film defects Raiszadeh and Griffiths [5] held a known volume of air in a melt of commercially pure liquid aluminum, and they recorded the change in its volume with time using real-time X-ray radiography. These results showed that, first, the oxygen of the trapped air bubble reacted to form Al 2 O 3 , and then, second, the nitrogen reacted to form AlN.…”
Section: Introductionmentioning
confidence: 99%
“…A semiempirical mathematical model was derived using the oxygen and nitrogen reaction rates estimated in this experiment, and it was used to estimate the duration of the atmosphere within double-oxide film defects. [2] Only a general estimate of the size of the latter was possible, but this work suggested that the atmosphere of a typical double-oxide film defect in liquid commercial purity aluminum (with a low initial hydrogen content), might be consumed by reaction with the surrounding melt in about 7 to 77 seconds, depending on the assumptions made about volume and surface area of the defect.…”
Section: Introductionmentioning
confidence: 99%
“…First oxygen and then nitrogen of the trapped atmosphere of the defect came into contact and react with the surrounding Al melt through these cracks to produce Al 2 O 3 and AlN, respectively. Using a semi-empirical mathematical model, [5] they suggested that this process took a few seconds to 2 minutes, depending on the size of the oxide defect and the severity of the turbulence in the melt.…”
Section: Formation Of a Double Oxide Film Defect Inmentioning
confidence: 99%
“…The air trapped in a bifilm will be expected to lose its oxygen by continued oxidation of the matrix, followed by nitrogen that would react to form nitride, [53] leaving mainly argon. In this way, it seems possible that clouds of fine argon bubbles will be released into the melt.…”
Section: Spheroidal Graphite Iron (Sgi) (Ductile Iron)mentioning
confidence: 99%